The impact of tropospheric delay towards the accuracy of GPS height determination - Yahya, Mohd. Hafiz; Kamaruddin, Md. Nor (2007)
When Global Positioning System (GPS) satellite signals propagates through the earth’s neutral atmosphere, the radio signals are affected significantly by the variability of its refractive index, which causes primarily in the delay of the arrival, usually referred to as the tropospheric delay. Without proper compensation, the delay affects significantly to the accuracy of GPS derived position especially in height component therefore is a matter of concern for geodetic and other high accuracy applications.With a view to visualize any discrepancies on height component of GPS measurement due to the tropospheric delay, RINEX data of MyRTKnet from five GPS reference stations in Johor have been integrated with GPS and ground local meteorological observations. Being held at one of GPS point in UTM, changes made on the antenna height at each observation session. In order to determine the amount of GPS signal propagation delay, a computer program namely TROPO.exe has also been developed based on a refined Saastamoinen tropospheric model. Results show that the tropospheric delay is a distance-dependent error that will increase when the baseline lenght between two stations increases. Furthermore, it also varies with changes in meteorological condition of daily observation. Based on another test using simulated data, it is proved that the amount of tropospheric delay will decrease when the antenna height increases.